Stacking clusters in the ROSAT all-sky survey - Bartelmann, Matthias; White, Simon D. M. (Arxiv, 2002)
Ongoing and planned wide-area surveys at optical and infrared wavelengths should detect a few times 10^5 galaxy clusters, roughly 10% of which are expected to be at redshifts >~ 0.8. We investigate what can be learned about the X-ray emission of these clusters from the ROSAT All-Sky Survey. While individual clusters at redshifts >~ 0.5 contribute at most a few photons to the survey, a significant measurement of the mean flux of cluster subsamples can be obtained by stacking cluster fields. We show that the mean X-ray luminosity of clusters with mass M >~ 2 x 10^{14} M_sun/h selected from the Sloan Digital Sky Survey should be measurable out to redshift unity with signal-to-noise >~ 10, even if clusters are binned with Delta z=0.1 and Delta ln M ~ 0.3. For such bins, suitably chosen hardness ratio allows the mean temperature of clusters to be determined out to z ~ 0.7 with a relative accuracy of Delta T/T <~ 0.15 for M > 10^{14} M_sun/h.
Gesehen am 26.09.2017